Applicability of Raman spectroscopy as a tool in nuclear forensics for analysis of uranium ore concentrates - Ho Mer Lin, Doris; Manara, D.; Varga, Zs; Berlizov, A.; Fanghänel, Thomas; Mayer, K. (Radiochimica acta, 2013)
In the present study, the suitability of Raman spectroscopy for nuclear forensics is proven by a systematic investigation of laboratory-prepared synthetic and industrial uranium ore concentrate (UOC) samples, of different origin and with wide range of impurity content. Besides the identification of the compound type, the identification of process-related impurities observed in these samples is reported for the first time. Both handheld and laboratory Raman spectrometers were used in the measurements. The ability to measure different UOCs and the sufficient sensitivity of the handheld device demonstrate its usefulness in nuclear safeguards and nuclear security applications. Even more importantly in such a context, the likely identity of process-related impurities could be verified by Raman Spectroscopy in the present work, allowing to draw conclusions on the process history of the sample.
Gesehen am 07.03.2022